Genomics of grain quality in cereals - Henry,Robert J (2021)
Abstract: Rapid advances in genomics are providing the tools to determine the genetic basis of quality (both nutritional and functional) in cereals. This promises to allow increased rates of genetic gain in breeding by reducing the need for extensive end-product testing of new varieties. Many quality traits are the result of relatively recent human selection and are thus likely to be controlled by only a few major genes. This makes identification of these genes for use in breeding selection an attractive target for breeders. Examples of the discovery of genes that are major contributors to key grain quality attributes include, fragrance and cooking temperature in rice (identified by re-sequencing) and loaf volume and milling yield in wheat (identified by transcriptome analysis). Extension of genomic tools to an analysis of the wider gene pool including wild relatives will enable the identification of alleles that may contribute to improved or novel grain quality in the future and may be critical to ensuring quality is retained in a changed climate. Completely new cereal species might be produced.